PEMUDA AFULU MENYONGSONG PEMILU: EDUKASI DAN SOSIALISASI PEMILIHAN UNTUK GENERASI MUDA - Agnes Lestariani Lase (Haga : Jurnal Pengabdian Kepada Masyarakat, 2023)
The "Education and Socialization of Elections for the Youth" program aims to increase awareness and voter participation among the youth of Afulu ahead of the elections. Utilizing methods such as workshops, election simulations, and social campaigns, this initiative engaged over 200 participants from various backgrounds. Evaluation results show a significant improvement in participants' understanding of the electoral process, their rights and responsibilities as voters, and the impact of political decisions. The program also successfully created a positive atmosphere that encouraged active involvement. Despite challenges such as diverse levels of understanding among participants, this activity made a meaningful contribution to the political education of the youth. It is hoped that this program can continue to foster informed and responsible voters in the future.